Uji In Silico Interaksi Senyawa Tropis Alami dan Sintetik Terhadap Protein Bcl-2 Sebagai Agen Antikanker Payudara: In Silico Study of Tropical and Synthetic Compounds Targeting Bcl-2 Protein as Breast Cancer Therapeutic Agents - Stefany Therisia; Masriani Masriani (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2025)
Breast cancer remains the leading cause of death among women worldwide. Resistance to chemotherapy and adverse effects of conventional treatments have driven the search for alternative therapeutic agents derived from natural compounds. One of the key molecular targets involved in cancer cell apoptosis is the Bcl-2 protein family. This study aimed to systematically review in silico molecular docking studies of natural compounds from tropical plants and synthetic molecules targeting the Bcl-2 protein as potential therapeutic agents for breast cancer. A total of 21 original research articles published in the last five years were analyzed based on the source of compounds (plant-derived or synthetic), active constituents, protein database (PDB) codes, and binding affinity values. The results indicated that most compounds demonstrated strong inhibitory potential against Bcl-2, with notable examples such as Niaziminin B from Moringa oleifera (−14.96 kcal/mol) showing one of the highest binding affinities. This review highlights the potential of natural compounds from tropical plants and synthetic molecules as promising candidates for breast cancer therapy through Bcl-2 inhibition. Further in vitro and in vivo studies are required to confirm their biological activity and toxicity profiles in the drug development process. Keywords: Breast cancer; Bcl-2; Molecular docking; Tropical plants; Synthetic compounds.